2018
DOI: 10.1016/j.ijsu.2018.06.035
|View full text |Cite
|
Sign up to set email alerts
|

The effect of the cerclage wire in the treatment of subtrochanteric femur fracture with the long proximal femoral nail: A review of 52 cases

Abstract: Open reduction and the use of cerclage did not produce a negative effect in terms of fracture union. The generation of medial support by anatomical reduction of the fracture prevents the implant failure and provide a basis for union.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 36 publications
3
19
0
Order By: Relevance
“…In the present study, one or two cerclages were used in the majority of cases (85%), while three cerclages remained the exception (15%). This is in line with recent studies, where also mainly one cerclage was used [32][33][34][35]. In our setting, the use of additional cerclage wiring meanwhile is considered as gold standard with more than 80% of AO/OTA type A3 fractures treated using this technique.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In the present study, one or two cerclages were used in the majority of cases (85%), while three cerclages remained the exception (15%). This is in line with recent studies, where also mainly one cerclage was used [32][33][34][35]. In our setting, the use of additional cerclage wiring meanwhile is considered as gold standard with more than 80% of AO/OTA type A3 fractures treated using this technique.…”
Section: Discussionsupporting
confidence: 87%
“…If anatomical reduction cannot be achieved sufficiently, the biomechanical basis for the necessary stability and the subsequent bone healing is missing. The supplemental use of cable cerclage wiring also reduces the risk of secondary varization of the axis and related complications [32][33][34][35]. The current study can contribute to this key point to the extent that the results have confirmed the above-mentioned intrinsic stability clinically.…”
Section: Discussionsupporting
confidence: 54%
“…Afsari, A et al believe that the proper use of cerclage cables for clamp-assisted reduction and intramedullary nail xations can achieve a good reduction effect and high fracture healing rate [13]. Kulkarni proposed that open reductions combined with cerclage cables do not adversely impact fracture healing [16]. It has been reported that the e cacy of using minimally invasive cerclage cables to subtrochanteric fractures is similar to that of reverse intertrochanteric fractures [13].…”
Section: Discussionmentioning
confidence: 99%
“…In 1987, Fitzgerald documented excellent results of using cerclage wires in comminuted fractures of the femur [3]. Subsequently, successful procedures for comminuted fractures of the femur have been reported [4][5][6][7][8][9], and percutaneous wiring techniques are being continually improved [10][11].…”
Section: Introductionmentioning
confidence: 99%